2010
DOI: 10.1007/s10532-010-9389-1
|View full text |Cite
|
Sign up to set email alerts
|

Potential for bioremediation of agro-industrial effluents with high loads of pesticides by selected fungi

Abstract: Wastewaters from the fruit packaging industry contain a high pesticide load and require treatment before their environmental discharge. We provide first evidence for the potential bioremediation of these wastewaters. Three white rot fungi (WRF) (Phanerochaete chrysosporium, Trametes versicolor, Pleurotus ostreatus) and an Aspergillus niger strain were tested in straw extract medium (StEM) and soil extract medium (SEM) for degrading the pesticides thiabendazole (TBZ), imazalil (IMZ), thiophanate methyl (TM), or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 51 publications
(45 reference statements)
0
26
0
2
Order By: Relevance
“…Despite that, TBZ was completely degraded by the bacterial consortium in all cases, which is a desirable asset for future biodepuration applications where composite inocula might be applied for the clean-up of poly-contaminated wastewaters. In the only other study investigating the biodegradation of TBZ, the fungus Trametes versicolor failed to degrade TBZ when exposed to a mixture of pesticides (Karas et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Despite that, TBZ was completely degraded by the bacterial consortium in all cases, which is a desirable asset for future biodepuration applications where composite inocula might be applied for the clean-up of poly-contaminated wastewaters. In the only other study investigating the biodegradation of TBZ, the fungus Trametes versicolor failed to degrade TBZ when exposed to a mixture of pesticides (Karas et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…To date, biotransformations have been the main focus in research on organophosphate pesticide degradation. Studies on pesticide metabolism by other fungi such as Aspergillus niger degrading Chlorpyrifos (Karas et al 2011), pyrethroid (Liang et al 2005), fenitrothion (Kanaly et al 2005), dimethoate (Liu et al 2001) and Aspergillus flavus for metolachlor (Sanyal and Kulshrestha 2004) are also reported. Moreover, Phanerochaete chrysosporium, Trametes versicolor and Pleurotus ostreatus for Chlorpyrifos degradation are reported (Karas et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The mixtures were subsequently passed through a 0.45 µm syringe filter (Sartorius Stedim Biotech GmbH Goettingen Germany) and the filtrates were used for HPLC analysis followed the methodology proposed by Karas et al, (2011). The HPLC system consisted of a Hewlett-Packard 1100 pump (Palo Alto, CA, USA) connected to a Hewlett-Packard 1046 programmable fluorescence detector, interfaced to a Hewlett-Packard Chem Station.…”
Section: Chlorpyrifos Degradation By a Oryzae On Synthetic Mediummentioning
confidence: 99%
“…Several authors have reported microorganisms, both fungi and bacteria, with the potential ability to degrade chlorpyrifos (Maya et al, 2012;Chishti et al, 2013;Dhanya, 2014). There is scarce information about chlorpyrifos tolerance or degradation by fungal strains (Omar, 1998;Karas et al, 2011;Maya et al, 2012), even more by Aspergillus spp. strains (Silambarasan and Abraham, 2013;Hindumathy and Gayathri, 2013;Yavad et al, 2014;Carranza et al, 2014).…”
Section: Chlorpyrifos Degradation In Synthetic Mediummentioning
confidence: 99%
See 1 more Smart Citation